Primary PCI in Elderly STEMI Patients: Risk Assessment and Management - Samiullah; Hameed Ullah; Abdul Waris; Khan, Muhammad Niaz; Nazeef Ullah; Abid Ullah (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate the impact of frailty on clinical and procedural outcomes in elderly STEMI patients undergoing primary percutaneous coronary intervention (PCI) at Hayatabad Medical Complex, Peshawar. Methodology: A retrospective study was conducted from April 2023 to March 2024, including 300 patients aged ≥65 years divided equally into frail and non-frail groups (n=150 each). Data were collected on demographic characteristics, procedural outcomes, and complications. Statistical analysis included chi-square tests for categorical variables and t-tests for continuous variables, with a significance level of p